Molecular characteristics and virulence gene profiles of Staphylococcus aureus causing bloodstream infection - Xuehan Li; Fang Fang; Jin Zhao; Ning Lou; Chenglin Li; Tao Huang; Yirong Li (Brazilian Journal of Infectious Diseases)
ABSTRACT Background: The rate of methicillin-resistant Staphylococcus aureus (MRSA) among the total of S. aureus isolates decreased to 35.3% in 2017 in China. It is unclear whether the molecular characteristics of S. aureus isolates have changed as the rate decreased. Objective: This study aimed to investigate the molecular characteristics and virulence genes profile of S. aureus isolates causing bloodstream infection and analyze the correlation between the prevalence rates of the common sequence types and MRSA. Methods: A total of 112 S. aureus strains from eight hospitals of four cities, including 32 MRSA isolates, were identified and evaluated through multilocus sequence typing, spa typing, and determination of virulence genes. Results: Twenty-five STs were identified, of which ST5 (21.4%) was the most prevalent, whereas the prevalence of ST239 correlated with the rate of MRSA among all S. aureus isolates. Forty-six spa types were identified, of which t2460 (14.3%) was the most common. clfa, hla, seb, fnbA and hlb were the prevailing virulence genes. 81.3% MRSA and 45.0% methicillin-sensitive S. aureus (MSSA) isolates harbored six or more tested virulence genes. ST5-t2460, seldom noted in bloodborne S. aureus isolates in China, was the most common clone. The prevalence of harboring six or more virulence genes in ST5-t2460 and ST188-t189 were 93.8% and 8.3%, respectively. Conclusion: ST5-t2460 was the most common clone in S. aureus causing bloodstream infection followed by ST188-t189, which had never been noted in China before. Moreover, ST5-t2460 harbored more virulence genes than ST188-t189, and the prevalence of ST239 clone decreased with the proportion of MRSA among all S. aureus isolates.